Prevalence and the impact of socioeconomic position on economic burden of asthma in rural adult residents of Yunnan province: a comparison between 2011 and 2021 - Lan LIU; Guohui LI; Chenghuan SUN; Yi MO; Jinbo LI; You HUANG; Qin LI; Mei ZUO; Le CAI (Zhongguo gonggong weisheng, 2023)
ObjectiveTo compare the prevalence of asthma and the impact of socioeconomic position (SEP) on economic burden of asthma among rural residents in Yunnan province in 2011 and 2021, and to provide evidence for the prevention and treatment of asthma in the population. MethodsUsing stratified multistage random sampling, we conducted face-to-face surveys during 2011 and 2021 among 8 187 and 7 572 rural residents aged ≥ 35 years in Yunnan province. A self-designed questionnaire was used to collect information on demographics, SEP, asthma clinically diagnosed at township and upper level hospitals, and asthma-related economic burden for analyses on asthma prevalence and the influence of SEP on asthma-induced economic burden among the participants. ResultsAmong the rural adults surveyed in 2011 and 2021, totally 111 and 122 asthma cases were identified, with the asthma prevalence rate of 1.36% and 1.61% and without significant difference between the two prevalence rates. Compared to those reported by the adults with asthma incidence in 2011, significantly higher per capita asthma-related direct cost (4 230.11 vs. 2 776.85 Chinese Yuan), indirect cost (69.57 vs. 49.86), and total cost (4 299.68 vs. 2826.71) were reported by the adults with asthma incidence in 2021 (all P < 0.05). Contrasting to that in 2011, the per capita asthma-related total cost increased significantly in 2021 for the asthma sufferers of various SEP groups (P < 0.05 for all) and the total cost increment varied in a descending order for the asthma sufferers with high, low, lower-middle, and upper-middle SEP. Conclusion Among the rural adult residents in Yunnan province, the prevalence of asthma was not significantly different but the economic burden of asthma sufferers increased substantially between 2011 and 2022 and the sufferers' economic burden varied with their socioeconomic position.